National Strategic Project Policy in the Jokowi Era: Exploring Underrated and Overrated Projects in Indonesian Development - Amin Amin; Rafi Imam Mahir; Ida Hindarsah (Jurnal Multidisiplin Sahombu, 2025)
The National Strategic Projects (PSN) policy is a key part of the infrastructure and economic development agenda under President Joko Widodo. This article aims to examine PSN projects considered underrated. and "overrated" based on impact, media coverage, and public perception. The research was conducted using a literature study and mass media analysis approach. The results of the study indicate that several projects, such as the Trans-Sumatra Toll Road and the SATRIA Satellite, have significant impacts but receive less attention (underrated), while projects such as the Jakarta-Bandung High-Speed Rail and the Food Estate receive more attention but are underrated. rated less optimal (overrated). Study This underline importance evaluation critical of strategic projects for the effectiveness of national development.